1989
DOI: 10.1159/000118559
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Potentials and Visual Spatial Attention: Influence of a Cholinergic Drug

Abstract: The effects of two dosages (200 mg, 600 mg, placebo) of a cholinergic nootropic (WEB 1881 FU) were investigated in a visual spatial attention task. Event-related brain potentials (ERPs) were used as a physiological measure of attention as they have previously been shown to be sensitive to allocation of attention to points in space. The typical enhancement of several peaks of the visual ERP due to attention was found in the present experiment. No systematic effect of the medication was revealed, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Scopolamine induces deficits characterized by reduced amplitudes and increased peak latencies (Meador et al 1989). It can be expected that cholinergic stimulation would enhance amplitudes (nonselective compounds: Dierks et al 1994;Münte et al 1988Münte et al , 1989, although for the auditory modality, a role for nicotinic receptors is less evident (Houlihan et al 1996). We cannot determine whether the lack of improvement is related to the small sample size or a ceiling effect in the groups of healthy volunteers.…”
Section: Discussionmentioning
confidence: 91%
“…Scopolamine induces deficits characterized by reduced amplitudes and increased peak latencies (Meador et al 1989). It can be expected that cholinergic stimulation would enhance amplitudes (nonselective compounds: Dierks et al 1994;Münte et al 1988Münte et al , 1989, although for the auditory modality, a role for nicotinic receptors is less evident (Houlihan et al 1996). We cannot determine whether the lack of improvement is related to the small sample size or a ceiling effect in the groups of healthy volunteers.…”
Section: Discussionmentioning
confidence: 91%
“…The main effects of the initial values were recognized for NlOO at Fz (F=6.34, P < 0.05), Cz (F=8, P<0.05) and Pz (F=8.03, P < 0.05) for rare stimuli and at Fz ( F = 3.77, P<O.l), Cz (F=4.56, P<0.05) and Pz ( F = 9.7, P < 0.01) for frequent stimuli; for P200 at Cz (F=8.05, P<0.05) and Pz (F=16.12, P<O.Ol) for rare stimuli, and at Fz ( F = 10.91, P<O.Ol), Cz (F=8.34, P<0.05) and Pz (F=8.67, P<O.Ol) for frequent stimuli; for N200 at Fz (F=3.72, P<O.l), Cz ( F = 15.22, P<O.Ol) and Pz for rare stimuli ( F = 21.04, P<O.001); and for P300 at Fz ( F = 5.32, P<0.05), Cz ( F = l l . l l , P<O.Ol) and Pz for rare stimuli [F=10.19, P<O.Ol, df ( 1,16) in every analysis] .…”
Section: Effects Of Initial Values (Values After Placebo) On Drug Resmentioning
confidence: 99%
“…The peak amplitudes of the ERP components by LAG and HAG are shown in Table 2. Statistical analyses showed that the main effect of the group was detected for NlOO at Fz ( F = 5.17, P<O.O5) for rare stimuli and at Pz ( F = 5.75, P<O.O5) for frequent stimuli; for P200 at Cz (F=4.75, P<0.05) and Pz ( F = 10.79, P<O.Ol) for rare stimuli and at Fz (F=5.68, P<0.05) and Pz (F=6.41, P<0.05) for frequent stimuli; for N200 at Fz ( F = 10.23, P < O.Ol), Cz (F=15.22, P<O.Ol) and Pz (F= 26.03, P<O.OOl) for rare stimuli; and for P300 at Fz (F=7.1, P<0.05), Cz ( F = 11.44, P<O.Ol) and Pz (F=8.36, P<0.05) for rare stimuli [df ( 1,16) in every analysis] .…”
Section: Effects Of Initial Values (Values After Placebo) On Drug Resmentioning
confidence: 99%